Transmission of 'Candidatus Phytoplasma pyri' by naturally infected Cacopsylla pyri to peach, an approach to the epidemiology of peach yellow leaf roll (PYLR) in Spain. (29th January 2018) - Sabaté, J.; Rodon, J.; Artigues, M.; Laviña, A.; Batlle, A.
Abstract : Peach orchards in the northeast of Spain were severely affected in 2012 by a previously unreported disease in this area. The symptoms included early reddening, leaf curling, decline, abnormal fruits, and in some cases death of the peach trees. All the infected peach samples were positive for ' Candidatus Phytoplasma pyri', but none were infected by the ' Ca . Phytoplasma prunorum'. In this work, potential vectors able to transmit ' Ca . Phytoplasma pyri' from pear to peach and between peach trees were studied and their infective potential was analysed at different times of the year. Transmission trials of the phytoplasma with potential vectors to an artificial feeding medium for insects and to healthy peach trees were conducted. Additionally, isolated phytoplasmas were genetically characterized to determine which isolates were able to infect peach trees. Results showed that the only insect species captured inside peach plots that was a carrier of the ' Ca . Phytoplasma pyri' phytoplasma was Cacopsylla pyri . Other insect species captured and known to be phytoplasma transmitters were present in very low numbers, and were not infected with ' Ca . Phytoplasma pyri' phytoplasma. A total of 1928 individuals of C. pyri were captured in the peach orchards, of which around 49% were phytoplasma carriers. All the peach trees exposed to C. pyri in 2014, and 65% in 2015, were infected by ' Ca . Phytoplasma pyri' 1 year after exposure, showing that this species is able to transmit the phytoplasma to peach. Molecular characterization showed that some genotypes are preferentially determined in peach.